Management Of Ellis Class II Fracture Of Maxillary Anterior Tooth With Composite Resin Restoration - Sidiartha, I Gusti Ayu Fienna Novianthi; Dewi, Made Kristiana (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Traumatic dental injury is a common dental health problem in society. Recovery from an anterior tooth fracture requires restoration that matches the appropriate color, anatomical shape, translucency, and alignment with the adjacent teeth in the arch. The restored tooth must adapt both aesthetically and functionally. Case: A 17-year-old female patient presented to the Udayana University Dental and Oral Hospital with a complaint of a broken front tooth. The tooth had been fractured approximately three years ago due to a collision. Clinical examination revealed crown fractures of teeth 11, 12, and 21. Vitality tests were positive, while percussion and mobility tests were negative. Case Treatment: Restoration was performed using A2 shade composite resin applied with an incremental technique. Finishing and polishing were carried out using a round-ended tapered fine finishing bur, Sof-Lex discs, and polishing strips for the proximal surfaces. Discussion: Crown fractures of anterior teeth are the most common type of trauma to permanent teeth, and they can result in aesthetic, psychological, social, and functional issues. Composite resin restorations are an appropriate treatment choice for such fractures due to their advantages, which include excellent esthetic outcomes, favorable physical and mechanical properties, and biocompatibility. Conclusion and Suggestions: Thorough examination and accurate diagnosis are essential for selecting the most appropriate treatment. Proper composite resin application techniques are crucial for the success of the restoration. Consequently, composite resin restorations can adapt well within the oral cavity, effectively restoring aesthetics, speech, and physiological function.